Saint Catherine’s Tormentum Rotarum Depiction at the Church of Saint Sebastian in the Roads in Toledo - de Mingo Lorente, Adolfo (Eikón / Imago, 2015)
The church of Saint Sebastian in the Roads, one of the oldest temples in Toledo, very close to the old seat of College and University of Saint Catherine (founded in 1485), preserves on its walls the most complete representation of the iconographic system of this saint in this city. Its state of conservation is severely deficient, but allows clearly to identificate several scenes in Jacobo de Voragine’s Golden Legend book, from among them the famous martyrdom with toothed wheels.